Research of thermal dynamic characteristics for variable load single screw refrigeration compressor with different capacity control mechanism. (5th January 2017) - Wang, Zengli; Wang, Zhenbo; Wang, Jun; Jiang, Wenchun; Feng, Quanke
Highlights: Theoretical models of SSRC under part-load condition have been established. The experiment of SSRC performance under part-load condition was conducted. Thermal dynamic characteristic of SSRC under part-load condition was gained. Economy and reliability of SSRC under part-load condition was analyzed. Abstract: In the single screw refrigeration compressor (SSRC), the capacity control mechanism is normally employed to meet the actual required cooling capacity under different load conditions. In this paper, theoretical calculation models describing the working process of the SSRC with the single slide valve capacity control mechanism (SVCCM) and SSRC with the frequency conversion regulating mechanism (FCRM) are established to research the thermal dynamic characteristics for variable load SSRC under part-load conditions. Experimental investigation on a SSRC under part-load conditions is also carried out to verify the theoretical calculation models. By using these validated models, the thermodynamic performances and dynamic characteristics of the SSRC with different capacity control mechanism under part-load conditions have been analyzed and compared. Through the comparison, the economical efficiency and reliability of the SSRC with different capacity control mechanism were obtained. All of these works can provide the basis for the later optimization design for the variable load single screw refrigeration compressor.